Transmastoid Occlusion Surgery for Superior Semicircular Canal Dehiscence Syndrome Improves Patient-Reported Quality-of-Life Measures and corrects cVEMP Thresholds and Amplitudes. Issue 10 (December 2021) - de Wolf, Maarten J. F.; Dawe, Nicholas; Jervis, Suzanne; Kumar, Raghu; Dalton, C. Lucy; Lindley, Karen; Irving, Richard
Abstract : Objective: To determine the pre- and postoperative clinical, audiological, vestibular, and patient-reported measures in patients undergoing transmastoid occlusion surgery for superior canal dehiscence syndrome (SCDS). Study Design: Retrospective case review. Setting: Tertiary referral centre, UK. Patients: All primary transmastoid occlusion surgeries for SCDS were included (tertiary centre, single-surgeon), January 2008 to July 2019. Interventions: Transmastoid superior canal occlusion surgery for SCDS. Main Outcome Measures: We collated audiological (pure tone audiogram), vestibular (cervical vestibular evoked myogenic potentials [cVEMPs]), and patient-reported outcome measures (Dizziness Handicap Inventory and subjective symptom grading). Results: Fifty-two patients (55 ears) met the inclusion criteria. Thirty-one (56%) were female. Mean age was 47 years (range 29–63) and mean follow-up of 11.2 months. Six patients had bilateral disease, four of whom underwent sequential, bilateral surgery. Autophony was the most frequent presenting symptom, improving in 92%. Significant improvements were self-reported in patients' autophony ( p  < 0.0001), pressure- and noise-induced dizziness ( p  < 0.0001 and p  < 0.0001), aural fullness ( p  = 0.0159), pulsatile tinnitus ( p  < 0.0001), perceived hearing loss ( p  = 0.0058), and imbalance ( p  = 0.0303). Overall Dizziness Handicap Inventory scores reduced from 45.9 to 27.4 ( p  < 0.0001), and across all subgroups of functional ( p  = 0.0003), emotional ( p  < 0.0001), and physical handicap ( p  = 0.0005). A 6.4-dB HL improvement in the air–bone gap (500–1000 Hz) occurred (95% confidence intervals 3.3–9.4 dB HL, p  < 0.0001). There were no dead ears. cVEMP thresholds, when recordable, normalized in all except two ears. Conclusions: Transmastoid occlusion is effective at improving patient-reported outcomes and normalizing cVEMP thresholds, though some symptoms, notably disequilibrium, persist to a variable degree. Abstract : Supplemental Digital Content is available in the text